PENGARUH MOTIVASI KERJA KEPALA SEKOLAH TERHADAP KEPUASAN KERJA GURU DI SMA NEGERI 1 MUTIARA - Nisaul Khaira (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
this study aims to determine the effect of work motivation principal on teacher job satisfaction together at SMA Negeri 1 Mutiara. This research uses a quantitative approach with associative methods. The analysis technique data used is simple and multiple linear regression analysis, T test and F test. The results showed that: There is a significant influence between the principal's work motivation on teacher job satisfaction by 79.1%. This means that work motivation will affect the job satisfaction of teachers in schools for the achievement of maximum performance; This means that the variable work motivation go hand in hand with teacher job satisfaction, meaning that the better the work motivation, the higher the teacher's job satisfaction. The principal's work motivation has a positive effect on teacher job satisfaction. It is appropriate for teachers to get things that can raise their enthusiasm in carrying out their duties, because a teacher will produce better performance if they have good work competencies and get sufficient work motivation